Initiation Village-Owned Enterprise for Strengthening Tourism Development - Panca Oktawirani; Teng-Yuan Hsiao (Journal on Tourism & Sustainability, 2020)
This study takes a perspective on the analysis of village owned enterprise involvement on tourism development in Tamansari, Indonesia. Using descriptive data, the paper aims to demonstrate that the driving force behind these enterprises is the need to improve the village economy such as optimizing village assets, developing community resources, and creating business opportunities. The qualitative study was undertaken between August - October 2019. It employed interviews with stakeholders (enterprise managers, local government, and residents of Tamansari).  Furthermore, the study utilised observation and secondary materials. This paper discusses preliminary findings regarding the study’s participants’ concerns in strengthening sustainability of tourism development in Tamansari.  Accordingly, the study develops the key factor role of village enterprise and how to gain the sustainability business community, and tourism development in local area.